The impact of greenwashing practices on green employee behaviour: Mediating role of employee value orientation and green psychological climate - Rubab Tahir (Taylor & Francis Group, 2020)
The awareness of environmental issues is rising among employees, customers, investors, and businesses. This study is focused on assessing the outcomes of practicing greenwashing and factors effecting green employee behaviour. A quantitative method was applied by collecting data from agri-inputs industry in Pakistan using survey (N = 520). The data were analysed by partial least square structural equation modelling in SmartPLS. Greenwashing has a negative impact on green employee behaviour with employee value orientation and green psychological climate negatively mediating (partially) this effect. The internal environmental orientation has no significant effect of mediation on the linkage of greenwashing and green employee behaviour. It is a cross-sectional study that might not have captured the constructs (e.g., greenwashing) fully. Besides, data were collected from one province and a single industry. It will help policymakers understand greenwashing effects and devising appropriate psychological strategies. The study emphasized on the holistic approach towards greening of organizations, and is, according to our best knowledge, the first empirical study that explored the impact of greenwashing on green employee behaviour in Pakistan.